Development of Technology-Based Sharia Insurance in Increasing Market Share in the Digital Era (Study at PT Chubb Life Medan Branch) - Afsari, Fidiya; Aqwa Naser Daulay,; Budi Dharma, (Jurnal Manajemen, 2023)
Technology is helping to make financial services more available to the general public at a lower cost. Technology development in financial institutions should be done methodically, with the aim of offering the best services to consumers through the use of advanced financial technology. Following the development of fintech in Indonesia, insurance technology (InsurTech) is also growing. Insurtech seeks to fundamentally and positively revolutionise the insurance industry through digital technology innovation. There are still problems that need to be addressed comprehensively to improve insurance digital literacy in Indonesia. Analysis can use a visual subjective strategy to ask about a proposal using qualitative methods. The source of data in this study is by conducting structured interviews, namely questions and answers that are carried out systematically and formally to an informant who is a Marketing Manager. The results showed that the development of technology-based Islamic insurance is the right strategy for PT Chubb Life Medan Branch to increase market share in the digital era. By implementing this strategy, the company can take advantage of existing opportunities and overcome its internal weaknesses. In conclusion, PT Chubb Life Medan Branch has a great opportunity to increase its market share in the digital era by developing technology-based Islamic insurance. Through online platforms, the company can reach a wider range of potential customers and market Islamic insurance products effectively. By implementing the right strategy, the company can overcome its weaknesses, take advantage of existing opportunities, and increase its market share.